2015
DOI: 10.1002/ece3.1381
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between morphological and molecular species boundaries among Caribbean species of the reef sponge Callyspongia

Abstract: Sponges are among the most species-rich and ecologically important taxa on coral reefs, yet documenting their diversity is difficult due to the simplicity and plasticity of their morphological characters. Genetic attempts to identify species are hampered by the slow rate of mitochondrial sequence evolution characteristic of sponges and some other basal metazoans. Here we determine species boundaries of the Caribbean coral reef sponge genus Callyspongia using a multilocus, model-based approach. Based on sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 89 publications
(189 reference statements)
2
18
0
Order By: Relevance
“…nov. collected in Bocas del Toro, Urabá, Cartagena and Santa Marta (continental shelf), than in specimens collected in San Andres or Martinique (oceanic islands). Similar variations in spicule sizes have been reported for other species collected in sites with low/high terrestrial runoff (Zea 1987, Debiasse & Hellberg 2015, Vicente et al 2016, Silva & Zea 2017.…”
Section: Discussionsupporting
confidence: 79%
“…nov. collected in Bocas del Toro, Urabá, Cartagena and Santa Marta (continental shelf), than in specimens collected in San Andres or Martinique (oceanic islands). Similar variations in spicule sizes have been reported for other species collected in sites with low/high terrestrial runoff (Zea 1987, Debiasse & Hellberg 2015, Vicente et al 2016, Silva & Zea 2017.…”
Section: Discussionsupporting
confidence: 79%
“…This was not surprising, as nucleotide substitution rates in the mitochondrial genome in sponges and other lower metazoans are up to 100 times slower than other animal lineages (Hellberg, 2006; Shearer et al, 2002). In this sense, although COI has been previously found to be useful to explain speciation and phylogeographic patterns in some haplosclerid sponges (see, for example, López-Legentil and Pawlik, 2009; DeBiasse and Hellberg, 2015), it seems to be unsuitable for resolving phylogenetic relationships in other sponges (see, for example, Duran et al , 2004; Dailianis et al , 2011). In light of these results, two possible explanations arise: the first one is that they are separate but closely related species that have undergone secondary contact favoring introgression, and a second explanation may be that I. variabilis and I. fasciculata are the same species but are currently undergoing incipient speciation without reproductive isolation yet occurring, and therefore a certain level of mixing still exists.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple analyses showed that some individuals from Central American populations were genetically divergent from sympatric C. vaginalis and might represent a cryptic species (Hart & Sunday, ). Phylogeographical studies on the Porifera frequently uncover cryptic species (Blanquer & Uriz, ; Xavier et al ., ; Andreakis et al ., ; de Paula et al ., ) likely because the morphological characters used to define sponges are simple and plastic and can vary geographically (Barnes & Bell, ; Loh & Pawlik, ; DeBiasse & Hellberg, ). Although the cryptic species sampled in Bocas del Toro and Utila had private mitochondrial haplotypes and nuclear alleles, it also shared a few nuclear alleles with C. vaginalis .…”
Section: Discussionmentioning
confidence: 99%